A study of pre-school children's school readiness related to skills of mathematics - (:unkn) unknown (HACETTEPE UNIV, 2007)
In this research, school readiness of children who had school readiness experiences and of children without experiences of school readiness were compared on the basis of scientific thinking skills in terms of age, gender, and socio economic status variables. The sample of the study consisted of 180 children with preschool education, and 120 children without pre-school education in the ages of 5, 5.5, and 6 years old. The data were gathered through the survey form that comprise personal information and by using subtest of math which belongs to implementation form of the Marmara Scale for Primary School Readiness. The findings were analyzed using t test and variance analysis. Results indicated that there is a significant difference between getting pre-school education and children's math skills. Children with pre-school education are more competent in terms of math skills than the children without pre-school education. In terms of gender, there was no significant difference regarding children's math skills. In terms of age, children's math skills were found to be different only with regards to sequencing and total score from the scale, and it was determined that in terms of math skills children of 5 years old are less competent than children of 5.5 and 6 years of age. The lower SES children were found to be disadvantageous in terms of primary school readiness regarding math skills.
Keywords: pre school education; school readiness; math skills